2017
DOI: 10.1016/j.ijdevneu.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced relative volume in motor and attention regions in developmental coordination disorder: A voxel‐based morphometry study

Abstract: Reduced relative volume in motor and attention regions in developmental coordination disorder: a voxel-based morphometry study.International Journal of Developmental Neuroscience http://dx.doi.org/10. 1016/j.ijdevneu.2017.01.008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 77 publications
(89 reference statements)
2
24
0
2
Order By: Relevance
“…Finally, different structural analyses have been conducted in previous studies to detect structural differences between DCD and TD groups. For example, Reynolds et al (2017) reported differences on grey matter volumes in frontal regions by using a voxel-based analysis. Further studies investigating structural differences, and more specifically cortical thickness, in larger number of DCD children are needed.…”
Section: Audio-verbal Synchronization During Learning Is Correlatedmentioning
confidence: 99%
“…Finally, different structural analyses have been conducted in previous studies to detect structural differences between DCD and TD groups. For example, Reynolds et al (2017) reported differences on grey matter volumes in frontal regions by using a voxel-based analysis. Further studies investigating structural differences, and more specifically cortical thickness, in larger number of DCD children are needed.…”
Section: Audio-verbal Synchronization During Learning Is Correlatedmentioning
confidence: 99%
“…Precuneus contribute to sensorimotor integration by combining multiple sensory inputs such as somatosensory and visual input, and involve in forming movement intention or early movement plans (Andersen and Buneo, 2002;Asher et al, 2015;Whitlock, 2017). Moreover, as part of the integrative center, PCC also participates in the motor and attention processes (Pearson et al, 2011;Reynolds et al, 2017). Therefore, the elevated fALFF and ReHo may consistently reflect compensatory neural adaptation of the PCC/precuneus for the movement control in HFS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the right lateral orbitofrontal cortex (BA11) and MFG (BA46) are more active in children with DCD (Caeyenberghs et al, 2016). The right precentral gyrus and medial frontal gyrus (BA6) showed a decline in activation in two studies (Reynolds et al, 2015a(Reynolds et al, , 2017, but in the study by Zwicker et al (2010) high activation was reported. In the pars opercularis of the IFG (BA44), children with DCD had lower activation during imitation and higher activation during observation than those in children with TD (Licari et al, 2015;Reynolds et al, 2015a).…”
Section: Frontal Lobementioning
confidence: 92%